2019
DOI: 10.14814/phy2.14257
|View full text |Cite
|
Sign up to set email alerts
|

Blue light at night acutely impairs glucose tolerance and increases sugar intake in the diurnal rodent Arvicanthis ansorgei in a sex‐dependent manner

Abstract: In our modern society, the exposure to light at night (LAN) has increased considerably, which may impact human health negatively. Especially exposure to light at night containing short wavelength emissions (~450–500 nm) can disrupt the normal function of the biological clock, altering sleep‐wake cycles and inducing metabolic changes. Recently, we reported that light at night acutely impairs glucose tolerance in nocturnal rats. However, light at night in nocturnal rodents coincides with their activity period, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 55 publications
3
16
1
1
Order By: Relevance
“…Moreover, animals were fasted for a few hours before the glucose tolerance tests, and the fasting state not only changes the glucose response but also changes SCN activity (26,27). Moreover, when the Arvicanthis were not fasted (25) we did not observe any significant effects of ALAN on basal plasma glucose concentrations, whereas in the current experiment, we found that blue light reduced blood glucose. The difference between the effects of blue light on nonfasted blood glucose in these two experiments could be because Arvicanthis are diurnal rodents, whereas here we used nocturnal rats.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Moreover, animals were fasted for a few hours before the glucose tolerance tests, and the fasting state not only changes the glucose response but also changes SCN activity (26,27). Moreover, when the Arvicanthis were not fasted (25) we did not observe any significant effects of ALAN on basal plasma glucose concentrations, whereas in the current experiment, we found that blue light reduced blood glucose. The difference between the effects of blue light on nonfasted blood glucose in these two experiments could be because Arvicanthis are diurnal rodents, whereas here we used nocturnal rats.…”
Section: Discussioncontrasting
confidence: 92%
“…Surprisingly, white and green light-exposed animals showed no significant changes in plasma glucose values. Previously, our laboratory showed that ALAN, especially white and green light, acutely impaired glucose tolerance in rats (12) and we observed a similar effect with blue light in the diurnal rodent Arvicanthis ansorgei (25). However, in both these experiments, a glucose tolerance test was used to investigate glucose metabolism, which prevents a direct comparison with the current results.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In the diurnal rodent Arvicanthis ansorgei, a single exposure to blue light at the beginning of the night (rest period) dysregulates glucose metabolism and induces feeding. In fact, animals exposed to 1 h of blue light and to a glucose tolerance test showed glucose intolerance and a reduced insulin secretion, possibly by a decreased beta cell activity [ 115 ]. No effects were observed on leptin concentrations by NLE.…”
Section: Nighttime Light Effects On Eating and Metabolism Of Diurnal Mammalsmentioning
confidence: 99%
“…Geceleri mavi yapay ışığa maruziyetin uyku-uyanıklık ve enerji metabolizmasının kontrolü üzerindeki etkisini değerlendirmeyi amaçlayan bir insan çalışması yapılmıştır. Bu çalışma sonucunda; enerji harcaması, oksijen tüketimi, karbondioksit üretimi ve kahvaltının termik etkisinin ışığa maruz kalmayan bireylere göre geceleri mavi yapay ışığa maruz kalanlar bireylerde önemli ölçüde düşük olduğu bildirilmiştir [21]. Düşük yağlı beslenen ve yüksek yağlı, yüksek sükrozlu beslenen dişi ve erkek fareler üzerinde geceleri mavi yapay ışığa (bALAN) maruz kalmanın etkileri ile ilgili yapılan çalışmanın sonuçları özellikle geceleri yapay ışığa maruz kalmanın erkek farelerde, uzun vadede diyabet gelişimine yol açabilen glikoz metabolizmasını bozduğunu göstermektedir.…”
Section: Mavi Işık Ve Sirkadiyen Ritimunclassified